2022
DOI: 10.3389/fonc.2022.844990
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hub Genes Associated With the Development of Stomach Adenocarcinoma by Integrated Bioinformatics Analysis

Abstract: ObjectiveThis study was conducted in order to gain a better understanding of the molecular mechanisms of stomach adenocarcinoma (STAD), which is necessary to predict the prognosis of STAD and develop novel gene therapy strategies.MethodsIn this study, the gene expression profile of GSE118916 in the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas Program (TCGA) was used to explore the differential co-expression genes of STAD and normal tissues.ResultsA total of 407 STAD samples were collected, consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Also, the top protein module of the PPI network of the N and NAT list were enriched in the same KEGG terms. These KEGG terms were also reported for GC by Lu et al [20], who analysed seven microarray datasets with NAT tissues as calibrators, Sun et al [21], who analysed the TCGA database, Li et al [22], who analysed two microarray datasets, Zhang et al [23], who analysed three microarray datasets, and Zhang et al [24], who analysed one microarray dataset and TCGA database. Also, the GO enrichment analysis was shown that DEGs in the N and NAT lists were enriched in some similar terms, such as extracellular matrix organisation, retinol metabolism, and metabolism of xenobiotics by cytochrome P450.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Also, the top protein module of the PPI network of the N and NAT list were enriched in the same KEGG terms. These KEGG terms were also reported for GC by Lu et al [20], who analysed seven microarray datasets with NAT tissues as calibrators, Sun et al [21], who analysed the TCGA database, Li et al [22], who analysed two microarray datasets, Zhang et al [23], who analysed three microarray datasets, and Zhang et al [24], who analysed one microarray dataset and TCGA database. Also, the GO enrichment analysis was shown that DEGs in the N and NAT lists were enriched in some similar terms, such as extracellular matrix organisation, retinol metabolism, and metabolism of xenobiotics by cytochrome P450.…”
Section: Discussionmentioning
confidence: 52%
“…[ 23 ], who analysed three microarray datasets, and Zhang et al. [ 24 ], who analysed one microarray dataset and TCGA database. Also, the GO enrichment analysis was shown that DEGs in the N and NAT lists were enriched in some similar terms, such as extracellular matrix organisation, retinol metabolism, and metabolism of xenobiotics by cytochrome P450.…”
Section: Discussionmentioning
confidence: 99%
“…GC is a malignant neoplasm affecting the gastrointestinal tract, characterized by a relatively high incidence and mortality. A signi cant proportion of patients present at an advanced stage upon diagnosis of GC, resulting in a 5-year survival rate ranging from only 11-40% [7]. Therefore, there is an urgent need for sensitive and speci c biomarkers for GC detection.…”
Section: Discussionmentioning
confidence: 99%
“…By integrated bioinformatics analysis in 2022, Zhang et al studied the stomach adenocarcinoma and introduced seven hub genes (EWSR1, ESR1, CLTC, PCMT1, TP53, HUWE1, and HDAC1) as related genes to occurrence of stomach adenocarcinoma [ 65 ]. Through a systems biology approach in 2022, Salarikia et al reported that medications such as pantoprazole, omeprazole, imatinib, troglitazone, fostamatinib, and amiloride might be useful in GC treatment.…”
Section: Discussionmentioning
confidence: 99%